Hubungan Kadar Ureum dan Kreatinin Dengan Kadar Hemoglobin (Hb) pada Penderita Diabetes Melitus Tipe 2 - Widiasih, Ni Kadek; Wiadnya, Ida Bagus Rai; Manu, Thomas Tandi; Kristinawati, Erna (Poltekkes Kemenkes Palembang, 2025)
Background: High blood sugar levels in people with diabetes mellitus will cause blockages and reduce the blood flow rate, thus decreasing the blood supply to the kidneys. This is indicated by high levels of urea and creatinine. Kidney damage leads to decreased production of the hormone erythropoietin, resulting in low oxygen levels and reduced red blood cell production, which can lead to anaemia.. Methods: This research method uses an analytical observation approach with a cross-sectional design. The sampling technique is non-random purposive sampling, Results: The results of the statistical test using the Spearman test showed a P value of 0.00 > 0.05, meaning that Ho is accepted and Ha is rejected. Conclusion: There is no relationship between urea and creatinine levels and haemoglobin (Hb) levels in people with type 2 diabetes mellitus.